The social function of property: A case of constitutional mutation in Peru? - Gutiérrez Merino, Franklin Gregorio (2025)
The liberal State emphasized that the right to property grants the attributes of using, enjoying, and disposing of an asset. However, beginning in 1911, Léon Duguit introduced the concept of the social function of property, asserting that the owner must not only seek personal satisfaction but also contribute to the well-being of the collective. Since its introduction, the social function of property has been incorporated into the constitutions of various states. However, the Peruvian constituent assembly of 1993 deliberately departed from this approach, and thus, Article 70 of our Constitution merely states that property shall be exercised in harmony with the common good—a provision that remains unchanged to this day. Consequently, the first objective of this research is to analyze the validity of the social function of property as a universal legal category within constitutional law. The methodology involved reviewing two rulings by the Constitutional Court of Spain and four rulings by the United States Supreme Court concerning property. In addition, five rulings by the Peruvian Constitutional Court were examined, in which the Court interpreted Article 70 of the Constitution—beyond its semantics—as a reference to the social function of property. This interpretative effort also allowed for the study of another constitutional law institution: constitutional mutation, for which thirty-six scholarly articles were reviewed. These findings reveal that the social function of property is present in both constitutions and court jurisprudence because it responds to a social reality. The conclusions confirm not only the validity of the concept of the social function of property, but also support the Peruvian Constitutional Court’s constitutional mutation with regard to Article 70 of the 1993 Constitution.